2004
DOI: 10.1021/ie049465e
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methodology toward Deep Desulfurization of Diesel Feed Based on the Selective Elimination of Nitrogen Compounds

Abstract: π-Acceptor molecules covalently attached on hydrophilic support were used to selectively remove neutral nitrogen heterocyclic compounds from diesel feed by a charge transfer mechanism. Functionalized hydrophilic polymers can effectively adsorb nitrogen heterocyclic compounds with a high selectivity toward sulfur heterocyclic compounds from model and real feed. The results showed that charge transfer processes coupled with an ion-exchange process to selectively remove basic nitrogen compounds are efficient enou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 53 publications
1
65
0
Order By: Relevance
“…[3][4][5] It was shown that the removal of nitrogen compounds from the middle-distillate oil significantly improve HDS performance, allowing one to achieve an ultra deep HDS under mild conditions using conventional catalysts. 6 The removal of nitrogen compounds by adsorption at ambient temperature is a promising approach. The adsorption of nitrogen compounds by well-known porous materials such as activated carbons, 7-9 activated alumina, 8,9 silica-based adsorbents 10,11 and zeolite-based materials 12,13 was studied ( Table 1).…”
mentioning
confidence: 99%
“…[3][4][5] It was shown that the removal of nitrogen compounds from the middle-distillate oil significantly improve HDS performance, allowing one to achieve an ultra deep HDS under mild conditions using conventional catalysts. 6 The removal of nitrogen compounds by adsorption at ambient temperature is a promising approach. The adsorption of nitrogen compounds by well-known porous materials such as activated carbons, 7-9 activated alumina, 8,9 silica-based adsorbents 10,11 and zeolite-based materials 12,13 was studied ( Table 1).…”
mentioning
confidence: 99%
“…In addition to sulfur compounds, diesel oil, gasoline and jet fuel contain many nitrogen-containing compounds [49]; the combustion of these substances will release large amounts of nitrogen oxides, leading to the formation of acid rain with serious environmental consequences [50]. Although the concentration of nitrogen-containing compounds in fuel oils is relatively low, the competition with sulfur-containing components for the active sites of the catalysts [51,52], can lead to the inhibition of the deep desulfurization process. Therefore, deep desulfurization and denitrogenation is of great significance for the development of clean oil products, and is a challenging task.…”
Section: Oxidation Catalystmentioning
confidence: 99%
“…Although the concentration of nitrogen-containing compounds in fuel oils is relatively low, the competition with sulfur-containing components for the active sites of the catalysts [51,52], can lead to the inhibition of the deep desulfurization process. Therefore, deep desulfurization and denitrogenation is of great significance for the development of clean oil products, and is a challenging task.…”
Section: Oxidation Catalystmentioning
confidence: 99%
“…(C 5 ) 3 N, C 5 -SH, and C 5 -NH 2 are formed as primary products by disproportionation and substitution of the reactants (similar to Eqs. (1) and (3)). C 1 -N(C 6 ) 2 reacted by substitution to C 1 -NH-C 6 , C 6 -NH-C 6 , and C 6 -SH as primary products (Eqs.…”
Section: Simultaneous Reaction Of C 5 -Nh-c 5 and C 1 -N(c 6 )mentioning
confidence: 99%
“…Nitrogen-containing compounds are harmful in deep HDS, as they inhibit the adsorption of sulfur-containing compounds [1][2][3] and, therefore, it is important to know how hydrotreating catalysts remove nitrogen-containing molecules.…”
Section: Introductionmentioning
confidence: 99%